Short-run fiscal policy: Welfare, redistribution, and aggregate effects in the short and long run - Sagiri Kitao (Federal Reserve Bank of New York, 2010)
This paper quantifies the effects of two short-run fiscal policies, a temporary tax cut and a temporary rebate transfer, that are intended to stimulate economic activity. A reduction in income taxation provides immediate incentives to work and save more, raising aggregate output and consumption. A temporary rebate is mostly saved and increases consumption marginally. Both policies improve the overall welfare of households, and the rebate policy especially benefits low-income households. In the long run, however, the debt accumulated to finance the stimulus and a higher tax to service the debt can crowd out capital and reduce output and consumption, causing welfare to deteriorate.
Keywords: E2; E62; H24; H6; 330; Short-run fiscal policy; life-cycle model; general equilibrium; Finanzpolitik; Lebenszyklus; Makroökonomischer Einfluss; Wohlfahrtsanalyse; Theorie